Alendronate and its Role in Post-Menopausal Osteoporosis - Sharma, Dilip; Yu, Deng; Shaobo, Zhu (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Alendronate (alendronic acid) is a nitrogen-containing drug that belongs to the second generation bisphosphonate class of drug. It binds to bone surfaces and inhibits bone resorption by osteoclasts and has been used as a treatment of choice in postmenopausal women with osteoporosis for many years. It is also a suitable drug for treatment of primary osteoporosis in men and for corticosteroid-induced osteoporosis in both men and women.1Oral alendronate (Alendronic acid) 5 or 10 mg/day has shown to produce an sustained increases in bone mineral density (BMD) in postmenopausal women with or without osteoporosis, in men with primary osteoporosis and in both men and women with or without osteoporosis receiving systemic corticosteroid therapy. Alendronic acid, administered at 70 mg once weekly or 35 mg twice weekly dose, has shown to increase the effective at increasing BMD as 10 mg/day and thus helps in the treatment or prevention of osteoporosis.In this review, I will be focussing mainly on the properties of oral alendronic acid in the treatment of post-menopausal osteoporosis.